The Effect of Concussion History on Lower Extremity Injury Risk in College Athletes: A Systematic Review and Meta-Analysis - Vanessa Ramirez; Ryan McCann; Eric Schussler; Jessica Martinez (North American Sports Medicine Institute, 2022)
# Introduction Collegiate athletes who suffer a concussion may possess prolonged impairments even after clearance for return-to-participation, which may place them at an increased risk of lower extremity injury. # Objective To conduct a systematic review and meta-analysis of studies examining risk of lower extremity musculoskeletal injury following a concussion in collegiate athletes. # Methods A literature search was performed using the following databases: PubMed, CINAHL, SPORTDiscus. The following search terms were used to identify relevant articles, \["concussion" OR "brain injury" OR "mild traumatic brain injury" OR "mTBI"\] AND \["lower extremity injury" OR "musculoskeletal injury"\]. Articles were included if they were published between January 2000 and July 2021 and examined collegiate athletes' risk of sustaining a lower extremity musculoskeletal injury following a concussion. Methodological quality of included studies was performed with a modified Downs and Black Checklist. The primary outcome of interest was the risk of sustaining a lower extremity musculoskeletal injury following a concussion. A random effects meta-analysis was conducted in which a summative relative risk (RR) for sustaining a lower extremity injury in athletes with and without a history of concussion was calculated. # Results Seven studies met the eligibility criteria to be included in the systematic review. There were 348 athletes in the concussion group and 482 control athletes in the included studies. Most of the studies were of good or excellent quality. Five of the seven studies were able to be included in the meta-analysis. College athletes who suffered a concussion possessed a 58% greater risk of sustaining a lower extremity musculoskeletal injury than those who did not have a history of a concussion (RR = 1.58[1.30, 1.93]). # Conclusions Lower extremity injury risk is potentially increased in college athletes following a concussion compared to those without a history of a concussion. Further research is needed to investigate the mechanism behind this increased risk. Clinical assessments throughout the concussion return-to-play protocol may need to be improved in order to detect lingering impairments caused by concussions. # Level of Evidence 1